Class war? : what Americans really think about economic inequality - Page, Benjamin I.; Jacobs, Lawrence R. (Chicago : University of Chicago Press, 2009)
Recent battles in Washington over how to fix America's fiscal failures strengthened the widespread impression that economic issues sharply divide average citizens. Indeed, many commentators split Americans into two opposing groups: uncompromising supporters of unfettered free markets and advocates for government solutions to economic problems. But such dichotomies, Benjamin Page and Lawrence Jacobs contend, ring false. In Class War? they present compelling evidence that most Americans favor free enterprise and practical government programs to distribute wealth more equitably. At every income le.
No class war -- Caring about economic inequality -- Looking to government for help -- Paying the bill -- Will policy makers respond? -- Appendix: the inequality survey.
Includes bibliographical references (pages 113-132) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Income distribution -- United States -- Public opinion; Public opinion -- United States; United States -- Economic conditions; United States -- Social conditions; United States -- Politics and government; Revenu -- Répartition -- États-Unis -- Opinion publique; Opinion publique -- États-Unis.; États-Unis -- Conditions économiques.; États-Unis -- Conditions sociales; États-Unis -- Politique et gouvernement; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Economics -- Macroeconomics; Economic history; Income distribution -- Public opinion; Politics and government; Public opinion; Social conditions; United States; Soziale Ungleichheit; Öffentliche Meinung; Einkommensverteilung; USA; Income distribution -- USA; Opinions -- USA; Public policy -- USA; USA -- economic conditions; USA -- social conditions; Electronic books